Low-temperature-resistant manganese iron lithium phosphate battery and preparation method thereof
Patent Information
- Application Number
- CN202610983934.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-03
- Publication Date
- 2026-10-09
AI Technical Summary
[0003]锂电子聚合物电池(LIPB)以聚合物电解质替代传统液态电解液,具备良好的耐低温能力,在零下40℃的低温环境下可以保持正常工作,由于低温环境下对现有的锂电子聚合物电池的电能传输效率造成影响,充放电能效出现下降,导致锂电子聚合物电池的工作状态下降,是目前新能源电池的主要问题之一,且现有的锂电子聚合物电池的电解质与正极材料的界面兼容性较差,界面阻抗较高,对锂离子传输效率造成影响
[0015]本发明提供了一种耐低温磷酸锰铁锂电池及其制备方法,通过生物模板在磷酸锰铁锂电池的正极材料中构建锂离子高速扩散通道,利用酵母模板的独特结构优势,构建了一个高效的锂离子传输和电子导电体系,使得锂离子在低温环境下也能通过多孔碳层和浸润其中的聚合物电解质层快速扩散,同时电子通过三维导电网络高效传输,从而显著降低了电池的整体内阻,提升了低温条件下的充放电性能。
Smart Images

Figure CN122889809A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery technology, specifically to a low-temperature resistant lithium manganese iron phosphate battery and its preparation method. Background Technology
[0002] Lithium manganese iron phosphate (chemical formula: LiMn) x Fe 1-x PO4 (LMFP), as a new generation of olivine structure cathode material, is regarded as an important development direction for improving the energy density of lithium-ion batteries because it combines the high safety and high cycle stability of lithium iron phosphate (LFP) with the high voltage platform (about 4.1V) brought by manganese.
[0003] Lithium-ion polymer batteries (LIPB) use polymer electrolytes instead of traditional liquid electrolytes, exhibiting good low-temperature resistance and maintaining normal operation in environments as low as -40°C. However, low temperatures affect the energy transfer efficiency of existing LIPB batteries, leading to a decrease in charge and discharge efficiency and a decline in the battery's performance. This is one of the main problems with current new energy batteries. Furthermore, existing LIPB batteries have poor interfacial compatibility between the electrolyte and the cathode material, resulting in high interfacial impedance, which also affects lithium-ion transport efficiency. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of the prior art. This invention provides a low-temperature resistant lithium manganese iron phosphate battery and its preparation method. By using yeast template as a growth guide, a high-speed lithium-ion diffusion channel is constructed in the positive electrode material, which can reduce the decline in lithium electron transport efficiency in low-temperature environments, thereby improving the working energy efficiency of the lithium battery.
[0005] This invention provides a low-temperature resistant lithium manganese iron phosphate battery, which includes: a negative electrode, a polymer electrolyte layer, a positive electrode, and an encapsulation layer arranged sequentially from the inside to the outside. The positive electrode is based on lithium manganese iron phosphate as the active material. The lithium manganese iron phosphate material includes several primary nanoparticles and several secondary micron-sized spherical particles. The primary nanoparticles and the secondary micron-sized spherical particles form a hierarchical microstructure. The hierarchical microstructure contains a three-dimensional interconnected ion diffusion channel formed based on yeast template growth, and the three-dimensional interconnected ion diffusion channel achieves full-domain connectivity by relying on the hierarchical microstructure. The gaps between the primary nanoparticles and the secondary micron-sized spherical particles are interconnected based on the three-dimensional through-flow ion diffusion channels. The positive electrode is tightly bonded to the polymer electrolyte layer, which is immersed in the three-dimensional through-channel ion diffusion of the positive electrode, forming a high-speed lithium-ion transport architecture.
[0006] Furthermore, the three-dimensional through-channel ion diffusion includes a number of mesopores and a number of channels, and a network structure in which the mesopores and channels are interconnected. The porosity of the network structure is α, and the value of α is in the range of 30%≤α≤40%.
[0007] Furthermore, the three-dimensional through-channel ion diffusion is formed based on an in-situ carbon layer, which covers the surface of the lithium manganese iron phosphate material of the cathode. The in-situ carbon layer is formed based on yeast template carbonization, and the in-situ carbon layer and the externally doped conductive agent of the positive electrode constitute a three-dimensional conductive network.
[0008] Furthermore, the external conductive agent is graphene, and the mass ratio of the amount of graphene added to the lithium manganese iron phosphate is β, wherein the value of β ranges from 4% to 6%.
[0009] Furthermore, the primary nanoparticle size of the lithium iron manganese phosphate material is d1, and the value of d1 is in the range of 50nm≤d1≤100nm; The particle size of the micron-sized secondary spherical particles is d2, and the value of d2 is in the range of 1μm≤d2≤5μm.
[0010] Furthermore, a polymer interface modification layer is provided between the positive electrode and the polymer electrolyte layer; The interface modification layer is a PEO polymer layer made of Al2O3 nano-ceramic filler. The room temperature ionic conductivity of the interface modification layer is γ, and the value of γ is in the range of γ≥10. -4 S / cm.
[0011] This invention also provides a method for preparing a low-temperature resistant lithium manganese iron phosphate battery, the method comprising the following steps: S1. Commercial yeast was used as a biological template to culture yeast in a culture medium, and the yeast raw material was activated to obtain an activated yeast template. S2. Prepare the precursor solution according to the preset stoichiometric ratio, and slowly add the activated yeast template suspension to the precursor solution at room temperature to obtain a mixed solution. S3. The mixed solution is heated to promote the formation of crystals on the cell wall of the yeast template by the precursor solution, and a yeast-precursor complex with nano-primary particles loaded on its surface is obtained. S4. Maintain the mixed solution in a neutral solution environment, stir slowly to promote the uniform coverage and reassembly of the primary nanoparticles on the yeast surface, and form a core-shell composite structure with micron-sized secondary spherical particles on the yeast template after vacuum drying. S5. The core-shell composite structure is placed in a tube furnace and subjected to high-temperature carbonization under the protection of high-purity inert gas, so that the yeast slowly decomposes and transforms the in-situ carbon layer covering the surface of the lithium manganese iron phosphate material to obtain a carbon composite material. S6. The carbon composite material and nitrogen-doped graphene nanomaterials are mixed at a preset mass ratio, ultrasonically dispersed in ethanol for 30 minutes, vacuum dried, and then heat-treated at high temperature under an inert atmosphere to obtain a three-dimensional conductive network structure. S7. The three-dimensional conductive network structure is combined with additives to prepare a positive electrode slurry. After coating, drying and rolling, a positive electrode substrate is obtained. The surface of the positive electrode substrate is modified to obtain a positive electrode sheet. S8. The negative electrode, polymer electrolyte layer, and positive electrode are stacked in sequence and then hot-pressed and sealed to obtain a lithium-ion polymer battery.
[0012] Furthermore, the method of using commercial yeast as a biological template to culture yeast in a culture medium, and activating the yeast raw material to obtain an activated yeast template includes: The yeast raw material was dissolved in deionized water, and the initial solution was obtained by thorough stirring. The initial solution was centrifuged at 3000 rpm to remove impurities, and after several washing operations, a pure solution was obtained. The pure solution was dried in a vacuum environment to obtain the activated yeast template.
[0013] Furthermore, the step of preparing the precursor solution according to a preset stoichiometric ratio, and slowly adding the activated yeast template suspension to the precursor solution at room temperature to obtain a mixed solution includes: A precursor solution was prepared by dissolving lithium acetate, manganese acetate, ferric acetate, and ammonium dihydrogen phosphate in deionized water according to a molar ratio of Li:Mn:Fe:P of 1:0.5:0.5:1. At room temperature, the activated yeast template suspension was slowly added dropwise to the precursor solution at a rate of 0.5 mL / min using a peristaltic pump, while magnetic stirring was performed continuously for 2 hours to obtain a homogeneous mixed solution.
[0014] Furthermore, the core-shell composite structure is placed in a tube furnace and subjected to high-temperature carbonization under the protection of high-purity inert gas, allowing yeast to slowly decompose and transform the in-situ carbon layer covering the surface of the lithium manganese iron phosphate material, resulting in a carbon composite material comprising: The core-shell composite structure is placed in a tube furnace, protected by high-purity inert gas, and heated to 300°C at a rate of 1-2°C / min, and held at that temperature for 2 hours for slow pre-carbonization. The yeast is slowly broken down and transformed into an in-situ carbon layer, while simultaneously forming a mesoporous network; The temperature is increased to 600-650℃ at a rate of 2-5℃ / min, and held for 6-12 hours to carry out high-temperature crystallization and orientation locking. At the same time, anti-site defects of lithium, iron and manganese elements are introduced to obtain carbon composite materials with three-dimensional through ion diffusion channels.
[0015] This invention provides a low-temperature resistant lithium manganese iron phosphate battery and its preparation method. By constructing a high-speed lithium-ion diffusion channel in the positive electrode material of the lithium manganese iron phosphate battery using a biological template, and utilizing the unique structural advantages of the yeast template, a highly efficient lithium-ion transport and electronic conductivity system is constructed. This allows lithium ions to diffuse rapidly through the porous carbon layer and the polymer electrolyte layer impregnated therein even at low temperatures. At the same time, electrons are efficiently transported through a three-dimensional conductive network, thereby significantly reducing the overall internal resistance of the battery and improving the charge and discharge performance under low-temperature conditions. Attached Figure Description
[0016] Figure 1 This is a schematic diagram of the internal structure of the low-temperature resistant lithium manganese iron phosphate battery in an embodiment of the present invention; Figure 2 This is a schematic diagram of the microstructure of the positive electrode material of the low-temperature resistant lithium manganese iron phosphate battery in an embodiment of the present invention; Figure 3 This is a flowchart illustrating the preparation method of a low-temperature resistant lithium manganese iron phosphate battery in this embodiment of the invention.
[0017] Figure reference numerals: 1. Positive electrode; 11. Primary microparticle; 12. Secondary spherical microparticle; 13. Three-dimensional through-hole ion diffusion channel; 2. Polymer electrolyte layer; 3. Negative electrode. Detailed Implementation
[0018] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0019] Example 1: Figure 1 A schematic diagram of the internal structure of a low-temperature resistant lithium manganese iron phosphate battery in an embodiment of the present invention is shown. Figure 2The diagram illustrates the microstructure of the positive electrode material in a low-temperature resistant lithium manganese iron phosphate battery according to an embodiment of the present invention. The low-temperature resistant lithium manganese iron phosphate battery includes, from the inside out, a negative electrode 3, a polymer electrolyte layer 2, a positive electrode 1, and an encapsulation layer, which are stacked sequentially. The negative electrode 3 undergoes an oxidation reaction during battery discharge and a reduction reaction during charging, while the positive electrode 1 undergoes a reduction reaction during battery discharge and an oxidation reaction during charging. Based on the polymer electrolyte layer 2 between the positive electrode 1 and the negative electrode 3, it can serve as a transport medium for lithium ions between the positive electrode 1 and the negative electrode 3, and at the same time provide electrical insulation, exhibiting good safety and flexibility.
[0020] The positive electrode 1 is based on lithium manganese iron phosphate as the active material. The lithium manganese iron phosphate material includes a number of primary nanoparticles 11 and a number of secondary micron spherical particles 12. The primary nanoparticles 11 and the secondary micron spherical particles 12 form a hierarchical microstructure. The primary nanoparticles 11 can provide more reactive sites, while the secondary micron spherical particles 12 can serve as a macroscopic framework to maintain the overall structural integrity of the electrode.
[0021] Specifically, the hierarchical microstructure contains a three-dimensional through-channel ion diffusion 13 formed by yeast template growth. The three-dimensional through-channel ion diffusion 13 achieves full-domain connectivity based on the hierarchical microstructure. The three-dimensional through-channel ion diffusion 13 is formed in the positive electrode 1 structure based on the yeast template, so that lithium ions can diffuse rapidly through the three-dimensional through-channel ion diffusion 13 during the operation of the lithium-ion polymer battery, thereby improving the working stability of the lithium-ion polymer battery in low-temperature environments.
[0022] Furthermore, yeast templates can serve as sacrificial templates during material synthesis. Their cellular structure is replicated by the material precursor and removed in subsequent processing, leaving behind a porous network corresponding to the yeast morphology. This porous network can be designed with pores of different sizes to meet the requirements of lithium-ion transport.
[0023] The gap between the primary nanoparticles 11 and the secondary micron spherical particles 12 is interconnected by the three-dimensional through ion diffusion channel 13. That is, the three-dimensional through ion diffusion channel 13 fills the gap between the primary nanoparticles 11 and the secondary micron spherical particles 12 of the cathode material, which can improve the migration and diffusion rate of lithium ions in the cathode material.
[0024] The positive electrode 1 is tightly bonded to the polymer electrolyte layer 2, which is immersed in the three-dimensional through-hole ion diffusion channel 13 of the positive electrode 1, forming a high-speed lithium-ion transport architecture. The cooperation between the three-dimensional through-hole ion diffusion channel 13 and the polymer electrolyte layer 2 effectively improves the lithium-ion transport efficiency of the lithium-ion polymer battery. This tight bonding and immersion design minimizes the interfacial impedance between the positive electrode 1 and the electrolyte, ensuring that lithium ions can efficiently enter the diffusion channels within the positive electrode material from the electrolyte layer.
[0025] Furthermore, this application achieves a tight bond between the positive electrode 1 and the polymer electrolyte layer 2, and fully immerses the polymer electrolyte layer 2 within the three-dimensional through-hole ion diffusion channel 13 of the positive electrode 1, forming a continuous high-speed lithium-ion transport architecture. Compared to the potential problems of poor interface compatibility and poor contact between the positive electrode 1 and the electrolyte in existing technologies, the solution of this application significantly reduces interface impedance and provides a seamless transport path for lithium ions from the electrolyte to the interior of the positive electrode 1. This synergistic effect of interface optimization and internal channels overcomes the challenges of high interface impedance and low ion transport efficiency at low temperatures.
[0026] Specifically, the low-temperature resistant lithium manganese iron phosphate polymer battery provided in this embodiment of the invention forms an efficient lithium-ion transport system by designing a specific microstructure for the cathode material, constructing ion channels in the cathode material, and optimizing the interface between the cathode 1 and the electrolyte. This system can effectively maintain the rapid transport of lithium ions in low-temperature environments, thereby ensuring the charge and discharge performance of the battery and providing a new solution for the development of low-temperature resistant lithium-ion battery technology.
[0027] Specifically, the three-dimensional through-channel ion diffusion system 13 comprises a plurality of mesopores and a plurality of channels, forming a network structure in which the mesopores and channels are interconnected. The porosity of the network structure is α, and the value of α ranges from 30% to 40%. The mesopores provide a large specific surface area, which is beneficial for the full wetting of the polymer electrolyte layer 2 and provides abundant adsorption and desorption sites for lithium ions, thereby promoting the rapid penetration of lithium ions into the cathode material. The formation of mesopores can be achieved by utilizing the micropores formed after carbonization of the bio-template during the material preparation process, or by controlling the self-assembly and sintering process of the precursor material.
[0028] The channels are macroscopic pores or through-channels with a diameter greater than 50 nanometers, which can significantly reduce the resistance to long-distance lithium-ion transport and ensure the rapid migration of lithium ions inside the cathode material. These channels can be formed through the macroscopic structure resulting from the carbonization of a bio-template, or prepared by introducing a pore-forming agent during the material synthesis process.
[0029] Multiple connection paths exist between mesopores and channels, forming a continuous and unobstructed ion transport network. This ensures efficient and multi-pathway transport of lithium ions within the cathode material, avoiding transport bottlenecks or localized ion accumulation that can occur with single-pore structures. This network structure can be achieved through naturally formed connections between yeast cells or within cell structures during the growth of the biological template, which are then preserved during subsequent carbonization; or by precisely controlling the crystallization and sintering processes to create a continuous spatial interconnection of pores at different scales. Porosity refers to the percentage of pore volume in a material's total volume. Controlling the porosity α of the network structure within the range of 30% to 40% aims to achieve an optimal balance between ion transport efficiency and material structural stability. If the porosity is too low, ion transport paths are limited, leading to decreased transport efficiency; if the porosity is too high, it may weaken the mechanical strength and structural stability of the cathode material, affecting the battery's cycle life. This porosity range can be achieved by precisely controlling process parameters such as the initial concentration of the yeast template, the ratio of the precursor solution, and the carbonization temperature and time.
[0030] By setting up a three-dimensional interconnected ion diffusion channel 13, the lithium-ion polymer battery can maintain good lithium-ion transport efficiency in low-temperature environments. By introducing an interconnected network structure composed of mesopores and channels, and precisely controlling its porosity within the range of 30% to 40%, the transport path of lithium ions within the cathode material is significantly optimized. Mesopores ensure sufficient contact between the polymer electrolyte layer 2 and the active material, and facilitate rapid lithium-ion penetration, while channels provide long-distance, rapid transport pathways. The two work synergistically to construct a highly efficient multi-level ion transport network. This optimized structure, while ensuring material structural stability, maximizes the lithium-ion transport rate in low-temperature environments, effectively reduces interfacial impedance, and thus significantly improves the charge-discharge performance and energy transfer efficiency of the low-temperature resistant lithium manganese iron phosphate battery under low-temperature conditions, ensuring stable battery operation in frigid environments.
[0031] Specifically, the three-dimensional through-channel ion diffusion 13 is formed based on an in-situ carbon layer, which covers the surface of the lithium manganese iron phosphate material of the cathode 1. The in-situ carbon layer is formed based on yeast template carbonization, and it, along with the externally doped conductive agent of the cathode 1, constitutes a three-dimensional conductive network. The in-situ carbon layer is formed by directly creating a carbonaceous coating on the surface of the active material during material synthesis or processing. This forming method ensures a high degree of bonding and interfacial stability between the carbon layer and the active material, providing a continuous and efficient transport path for lithium ions while protecting the active material and helping to maintain the integrity of the electrode structure.
[0032] Furthermore, growth control based on yeast templates allows the preparation of the positive electrode 1 of the lithium-ion polymer battery to be attached to the cell nucleus growth path of the yeast template. After high-temperature treatment, the yeast template is converted into an in-situ carbon layer. A precursor is used to decompose and deposit on the material surface to form a carbon layer, ensuring that the in-situ carbon layer can uniformly and tightly cover the surface of the lithium manganese iron phosphate material of the positive electrode 1. This can effectively reduce the interfacial impedance between the active material and the electrolyte and prevent the active material from undergoing side reactions with the electrolyte during cycling.
[0033] Furthermore, due to the natural micron-sized size and porous structure of yeast cells, during carbonization, the organic components of the yeast cells are converted into carbon, retaining their original morphology and pore structure, thus forming a carbon layer with three-dimensional interconnected ion diffusion channels 13. When the in-situ carbon layer combines with the externally doped conductive agent, they together form a three-dimensional conductive network covering the active material and penetrating the entire electrode. This network can effectively collect and transport electrons, ensuring rapid electron conduction between active material particles and between the active material and the current collector.
[0034] This invention, through the integration of a three-dimensional through-channel ion diffusion 13 with an in-situ carbon layer and leveraging the unique structural advantages of a yeast template, constructs a highly efficient lithium-ion transport and electronic conductivity system. Specifically, the in-situ carbon layer directly covers the surface of the lithium manganese iron phosphate material in the cathode 1. This tightly bonded structure ensures unimpeded ion transport at the interface between the active material and the carbon layer, effectively avoiding the increased impedance caused by interface separation in traditional methods. The in-situ carbon layer is formed based on the carbonization of the yeast template. The natural porous structure of yeast cells transforms into a carbon skeleton with abundant mesopores and channels after carbonization. These channels constitute the three-dimensional through-channel ion diffusion 13, providing numerous rapid transport paths for lithium ions. Simultaneously, the in-situ carbon layer is interconnected with the externally doped conductive agent added to the cathode 1, forming a three-dimensional conductive network that runs through the entire cathode material. This network not only provides efficient electron transport channels but also intertwines with the three-dimensional through-channel ion diffusion 13, forming a composite transport architecture that allows for rapid migration of both ions and electrons. This integrated design allows lithium ions to diffuse rapidly through the porous carbon layer and the polymer electrolyte layer 2 impregnated within it, even at low temperatures. At the same time, electrons are efficiently transported through a three-dimensional conductive network, which significantly reduces the overall internal resistance of the battery and improves the charge and discharge performance under low-temperature conditions.
[0035] Specifically, the external conductive agent is graphene, and the mass ratio of the added graphene to the lithium manganese iron phosphate is β, where β ranges from 4% to 6%. Graphene is a two-dimensional carbon nanomaterial composed of carbon atoms arranged in a hexagonal honeycomb lattice with sp² hybrid orbitals, possessing extremely high electronic conductivity, excellent mechanical strength, and a large specific surface area. As a conductive agent in cathode materials, graphene's main role is to construct efficient electron transport pathways, thereby significantly improving the overall electronic conductivity of the cathode material.
[0036] Based on the structure and properties of graphene, the requirements for constructing efficient three-dimensional conductive networks can be met. By limiting the mass ratio between graphene and lithium manganese iron phosphate, the construction of the conductive network can be optimized to balance conductivity and material structural stability. The graphene and lithium manganese iron phosphate can be uniformly dispersed using methods such as dry mixing or wet mixing (e.g., slurry mixing) to avoid excessive conductive agent occupying space in the active material or affecting lithium-ion transport.
[0037] The proposed solution utilizes graphene as an external conductive agent, precisely controlling its addition ratio, to construct a highly efficient three-dimensional conductive network together with the in-situ carbon layer on the surface of the cathode material. In the low-temperature resistant lithium manganese iron phosphate battery, the cathode material is based on lithium manganese iron phosphate, and a three-dimensional interconnected ion diffusion channel 13 based on yeast template growth has been formed inside. This three-dimensional interconnected ion diffusion channel 13 achieves full connectivity through a hierarchical microstructure, ensuring rapid lithium ion transport.
[0038] Furthermore, by introducing graphene as an external conductive agent, graphene, with its excellent conductivity and large specific surface area, can effectively bridge the tiny gaps in the in-situ carbon layer, thereby enhancing the electron transport efficiency between and within the cathode material particles.
[0039] Specifically, in preparing a single positive electrode for a low-temperature resistant lithium manganese iron phosphate battery, a carbon composite material (containing lithium manganese iron phosphate and an in-situ carbon layer) obtained through high-temperature carbonization can be mixed with nitrogen-doped graphene nanomaterials. For example, if the mass of lithium manganese iron phosphate in the carbon composite material is 100 parts, then 4 to 6 parts of nitrogen-doped graphene nanomaterials can be added. The two are ultrasonically dispersed in a dispersant such as ethanol at this mass ratio to ensure that the graphene is uniformly distributed on the surface of the lithium manganese iron phosphate particles and between the in-situ carbon layers. Subsequently, after vacuum drying and high-temperature heat treatment in an inert atmosphere, the graphene and the in-situ carbon layers are tightly bonded, forming a highly interconnected three-dimensional conductive network structure.
[0040] Specifically, by using graphene as an external conductive agent and precisely controlling its addition ratio, the electronic conductivity of the cathode material can be significantly enhanced, constructing a more stable and efficient three-dimensional conductive network. This effectively solves the problem of low conductive network efficiency caused by the unclear type and ratio of traditional external conductive agents, thereby reducing the interfacial impedance of the cathode material and promoting rapid electron transport. Especially in low-temperature environments, this optimized conductive network can maintain a high electron transport rate, effectively improving the battery's charge-discharge efficiency and power performance, and enhancing the reliability and cycle stability of low-temperature resistant lithium manganese iron phosphate batteries under severe cold conditions.
[0041] Specifically, in this embodiment of the invention, the primary nanoparticles 11 of lithium iron manganese phosphate have a particle size of d1, where d1 ranges from 50 nm to 100 nm. This nanoscale size endows the particles with a large specific surface area, significantly increasing the number of active sites for lithium ion adsorption and desorption at the solid-liquid interface, and effectively shortening the solid-phase diffusion path of lithium ions within the particles. This particle size control can be achieved by precisely adjusting parameters such as precursor concentration, reaction temperature, pH value, and reaction time during the synthesis of lithium iron manganese phosphate, thereby guiding the acquisition of the corresponding size parameters.
[0042] The micron-sized secondary spherical particles 12 have a particle size of d2, which ranges from 1 μm to 5 μm. These particles are micron-sized structures formed by the aggregation or self-assembly of multiple primary nanoparticles 11, with a particle size d2 limited to between 1 μm and 5 μm. This suitable micron-sized structure is crucial for constructing a stable and efficient hierarchical microstructure. It not only helps improve the tap density of the cathode material and enhances the electrode's processing performance, but the porous structure within the micron-sized secondary spherical particles 12, composed of primary nanoparticles 11, also provides a stable framework for the three-dimensional through-hole ion diffusion channels 13.
[0043] Spray drying, granulation, or self-assembly techniques can be employed. For example, during spray drying, the size and morphology of the secondary spherical particles 12 can be effectively controlled by precisely regulating the slurry concentration, spray pressure, atomizer type, and drying temperature.
[0044] Specifically, in preparing the cathode material for low-temperature resistant lithium manganese iron phosphate batteries, lithium manganese iron phosphate nanoparticles 11 can be synthesized using a hydrothermal method. By precisely controlling the reaction temperature at 180℃, the reaction time at 12 hours, and adjusting the concentration of the precursor solution, nanoparticles 11 with an average particle size of approximately 75 nm can be obtained.
[0045] Subsequently, these primary nanoparticles 11 are granulated using spray drying technology. By optimizing the spray pressure and drying temperature, for example, setting the spray pressure to 0.2 MPa and the inlet temperature to 200 °C, micron-sized secondary spherical particles 12 with an average particle size of approximately 3 μm can be formed. These primary nanoparticles 11 and micron-sized secondary spherical particles 12 with specific particle size ranges together constitute the hierarchical microstructure of the cathode material and form three-dimensional interconnected ion diffusion channels 13 with optimized internal dimensions.
[0046] Specifically, a polymer interface modification layer is provided between the positive electrode 1 and the polymer electrolyte layer 2 of the low-temperature resistant lithium manganese iron phosphate battery; the interface modification layer is a PEO polymer layer made of Al2O3 nano-ceramic filler, and the room temperature ionic conductivity of the interface modification layer is γ, wherein the value of γ is ≥ 10. -4 S / cm. The polymer interface modification layer is a functional thin layer disposed between the positive electrode 1 and the polymer electrolyte layer 2. Its function is to act as a buffer layer, which can effectively improve interface compatibility, reduce interface impedance, and optimize the lithium-ion transport path.
[0047] Furthermore, the interface modification layer can also be in the form of a PVDF-HFP (polyvinylidene fluoride-hexafluoropropylene) and SiO2 (silicon dioxide) nanocomposite film, or a PMMA (polymethyl methacrylate) and TiO2 (titanium dioxide) nanocomposite film, etc.
[0048] The PEO polymer layer, i.e., polyethylene oxide, possesses excellent ionic conductivity and flexibility, providing a matrix for lithium-ion transport. The Al2O3 nanoceramic filler, i.e., alumina nanoparticles, exhibits high chemical stability, mechanical strength, and thermal stability, enhancing the structural integrity of the interface layer, inhibiting lithium dendrite growth, and promoting lithium-ion dissociation and transport through its Lewis acid sites interacting with lithium salt anions. Besides Al2O3, other nanoceramic fillers such as SiO2, TiO2, and ZrO2, or other inorganic fillers with similar reinforcing and ion transport-promoting effects, can also be used.
[0049] The room temperature ionic conductivity of the interface modification layer is γ, and the value of γ is in the range of: γ≥10. -4 The S / cm parameter is set to ensure that the interface layer itself has sufficient lithium-ion transport capacity, preventing it from becoming a rate-limiting factor in the entire battery system. Especially at low temperatures, high ionic conductivity is crucial for maintaining battery performance, and this value range sets a minimum performance standard. The ionic conductivity of the interface modification layer can be achieved and controlled by optimizing the molecular weight and crystallinity of PEO, adjusting the content, particle size, and surface modification of Al2O3 nanofillers, and selecting appropriate lithium salts and additives.
[0050] Furthermore, by introducing a polymer interface modification layer between the positive electrode 1 and the polymer electrolyte layer 2, this interface modification layer acts as a buffer layer, effectively solving the problems of poor interface compatibility and high interface impedance when the positive electrode 1 and the polymer electrolyte layer 2 are in direct contact. This interface modification layer is composed of PEO polymer and Al2O3 nano-ceramic filler. PEO provides a flexible and ionically conductive matrix, while the Al2O3 nano-filler enhances the mechanical strength and thermal stability of the interface layer and may promote lithium-ion transport through its surface properties. This structural design allows lithium ions to cross the interface between the positive electrode 1 and the polymer electrolyte layer 2 more smoothly, reducing transport resistance. Simultaneously, this interface modification layer is designed to have a high room temperature ionic conductivity (γ≥10). -4 The interface modification layer (S / cm) ensures that it will not become a bottleneck for lithium-ion transport. Therefore, the interface modification layer, together with the three-dimensional through-channel ion diffusion channel 13 formed by yeast template inside the positive electrode 1 and the polymer electrolyte layer 2 impregnated therein, creates a highly efficient and stable high-speed lithium-ion transport architecture, which can effectively maintain the charge and discharge performance of the battery, especially in low-temperature environments.
[0051] This invention provides a low-temperature resistant lithium manganese iron phosphate battery and its preparation method. By constructing a high-speed lithium-ion diffusion channel in the positive electrode material of the lithium manganese iron phosphate battery using a biological template, the working efficiency of the lithium manganese iron phosphate battery in low-temperature environments is improved.
[0052] Example 2: Figure 3 A flowchart illustrating the preparation method of a low-temperature resistant lithium manganese iron phosphate battery according to an embodiment of the present invention is shown. The preparation method includes the following steps: S1. Commercial yeast was used as a biological template to culture yeast in a culture medium, and the yeast raw material was activated to obtain an activated yeast template. Commercial yeast is used as a biological template, its unique cellular structure serving as a growth site for nanoparticles and guiding the formation of specific microstructures in the material. Activation treatment of the yeast raw material aims to enhance its activity and surface reactivity, enabling it to more effectively adsorb precursors. Activation can be achieved through multiple centrifugations and washings to remove impurities, followed by resuspending in deionized water to ensure a clean yeast surface and good activity. Alternatively, specific yeast strains can be selected and cultured on optimized solid media to obtain high-density, morphologically uniform yeast cells. Activation treatment can employ mild acid-base or enzymatic treatments to expose more surface active sites and enhance its adsorption capacity for metal ions.
[0053] Specifically, yeast cells are cultured in a suitable nutrient environment to ensure they reach the required quantity and activity level. A series of purification steps remove impurities and enhance their biological activity, ultimately yielding a high-purity, highly active yeast cell population. Commercial yeast offers advantages such as uniform cell structure, ease of acquisition, and low cost. Its natural micron-sized structure and porous nature provide a natural skeletal support for the subsequent growth of lithium manganese iron phosphate materials, guiding the formation of specific hierarchical microstructures and three-dimensional interconnected ion diffusion channels.
[0054] Furthermore, yeasts such as Saccharomyces cerevisiae or Bacillus bakerella can be selected and cultured aerobically in YPD medium to optimize yeast growth and cell activity. Activation treatment aims to remove any impurities, dead cells, or metabolites that may be present in the yeast feedstock, and to enhance the biological activity of yeast cells, making their cell wall structure more readily interact with the precursor solution. This can be achieved through mild acid-base treatment, enzyme treatment, or pre-incubation in a specific buffer solution.
[0055] Yeast raw materials are dissolved in deionized water, and the initial solution is obtained by thorough stirring to avoid introducing other ionic impurities that could interfere with subsequent activation and material synthesis processes. Deionized water has extremely low conductivity and impurity content, ensuring maximum purity of the solution. Thorough stirring ensures that the yeast raw materials are uniformly dispersed in the deionized water, forming a non-agglomerated suspension, providing a homogeneous starting state for subsequent purification operations.
[0056] The initial solution was centrifuged at 3000 rpm to remove impurities. After several washing operations, a pure solution was obtained. Centrifugation was used to separate components with different densities or particle sizes. Centrifugation at 3000 rpm effectively precipitates yeast cells while retaining lighter impurities or incompletely dissolved substances in the supernatant, thus achieving preliminary purification. The process of centrifugation and redispersing in fresh deionized water was repeated. Each wash further removed residual impurities and metabolic products from the supernatant until the yeast cells reached a high purity state. In this embodiment, a benchtop centrifuge was used to centrifuge at the set speed for 10-15 minutes. Then, the yeast precipitate was redispersed in an equal volume of deionized water, vortexed, and centrifuged again. This process was repeated 2-3 times.
[0057] Drying a pure solution in a vacuum environment to obtain an activated yeast template involves drying at sub-atmospheric pressure, which lowers the boiling point of water and allows for rapid moisture removal at lower temperatures, preventing damage to yeast cell activity and structure from high temperatures. Simultaneously, the vacuum environment effectively prevents the yeast template from oxidation or exposure to other airborne contaminants during drying, ensuring its purity and stability. For example, a vacuum freeze dryer can be used to maximize the preservation of yeast's biological activity and structural integrity, or drying can be performed at lower temperatures in a vacuum oven.
[0058] S2. Prepare the precursor solution according to the preset stoichiometric ratio, and slowly add the activated yeast template suspension to the precursor solution at room temperature to obtain a mixed solution.
[0059] Prepare the precursor solution according to the preset stoichiometric ratio to ensure that the chemical composition of the final product meets the requirements. The precursor solution can be prepared by dissolving lithium, iron, manganese, and phosphorus sources in a Li:Mn:Fe:P molar ratio in deionized water or an ethanol / water mixture. Slowly add the activated yeast template suspension to the precursor solution at room temperature. This helps the yeast template to be uniformly dispersed in the precursor solution, avoids aggregation, and provides conditions for subsequent uniform crystallization. The yeast suspension can be added at a constant rate using a drop pump while magnetically stirring; alternatively, ultrasonic-assisted dispersion can be used during the addition of the yeast suspension to further improve the uniformity of the yeast template dispersion in the solution and ensure the homogeneity of subsequent reactions.
[0060] Furthermore, precise elemental proportions are fundamental to forming lithium manganese iron phosphate materials with ideal crystal structures and electrochemical properties. This can be achieved by accurately weighing the corresponding precursor salts (e.g., lithium, iron, manganese, and phosphate salts) and dissolving them in a solvent, or by using a pre-prepared high-purity composite salt solution. Adding a reducing agent to the initial precursor solution is crucial to prevent undesirable oxidation of certain metal ions (especially iron ions) in the precursor solution during subsequent reactions, which could affect the purity and structure of the final product. The reducing agent maintains the metal ions in their target valence state, providing a stable chemical environment for the subsequent crystallization process. Commonly used reducing agents include ascorbic acid, hydrazine hydrate, or certain organic acids such as citric acid. Adjusting the solution pH to neutral is also essential to maintain the activity of the yeast template and provide a suitable pH environment for the uniform crystallization of the precursor on the yeast surface. A neutral environment effectively avoids damage to the yeast cell wall structure from strong acids or bases, while also facilitating the adsorption and nucleation of precursor ions on the yeast template. The pH can be adjusted by adding dilute acid (such as dilute hydrochloric acid or dilute nitric acid) or dilute alkali (such as dilute sodium hydroxide or dilute ammonia) solutions, and monitored in real time using a pH meter. The activated yeast template suspension is slowly added to the precursor solution at room temperature. This ensures thorough and uniform mixing of the yeast template and precursor solution, avoiding localized excessive concentrations or violent reactions that might result from rapid mixing. Room temperature helps maintain the bioactivity and structural stability of the yeast template, while avoiding the impact of temperature fluctuations on the crystallization process. Slow addition can be achieved through dripping, pumping, or using a constant-speed stirrer with a feed pipe to ensure a smooth mixing process. The final result of all the above operations is a homogeneous and stable mixed system in which the activated yeast template is uniformly dispersed and in full contact with the precursor ions. This mixed solution is a key precursor for the subsequent formation of primary nanoparticles and secondary micron-sized spherical particles on the yeast template.
[0061] S3. The mixed solution is heated to promote the crystallization of the precursor solution on the cell wall of the yeast template, thereby obtaining a yeast-precursor complex with nano-primary particles loaded on its surface.
[0062] Heating the mixed solution provides the activation energy required for the reaction, accelerating the heterogeneous nucleation and growth of precursors on the yeast cell wall surface, forming nanoscale lithium manganese iron phosphate primary particles. The yeast cell wall serves as a natural template, and its abundant functional groups can adsorb metal ions, inducing crystallization. Heating can be achieved by placing the mixed solution in a water bath or oil bath and heating it to a preset temperature at a controlled rate, maintaining this temperature for a certain time to allow the precursors to fully crystallize on the yeast surface; alternatively, microwave-assisted heating can achieve rapid and uniform heating, promoting rapid nucleation and growth of precursors on the yeast template, thereby more effectively controlling the size and morphology of the primary nanoparticles.
[0063] S4. Maintain the mixed solution in a neutral environment, stir slowly to promote uniform coverage and reassembly of the primary nanoparticles on the yeast surface, and form a core-shell composite structure with micron-sized secondary spherical particles on the yeast template after vacuum drying.
[0064] Maintaining the mixed solution in a neutral environment is beneficial for the stable precipitation and growth of lithium manganese iron phosphate, avoiding damage to the yeast template or influence on product morphology caused by acidic or alkaline environments. Slow stirring helps the primary nanoparticles to be uniformly adsorbed and reassembled on the yeast surface, forming a denser coating layer and ultimately constructing micron-sized secondary spherical particles. Vacuum drying removes moisture and solidifies the core-shell structure. The neutral environment can be precisely adjusted and maintained at a pH between 6.5 and 7.5 by adding dilute acid or alkali solutions, while keeping the stirring speed low to avoid damaging the formed nanoparticles. Vacuum drying can be carried out at a low temperature for several hours to obtain the core-shell composite structure.
[0065] Furthermore, a pH buffer solution can be used to maintain a neutral environment and ensure pH stability. During the stirring process, planetary stirring or drum stirring can be used to achieve a gentler and more uniform mixing. After vacuum drying, freeze drying can be carried out to better maintain the pore structure of the material.
[0066] S5. The core-shell composite structure is placed in a tube furnace and subjected to high-temperature carbonization under the protection of a high-purity inert gas. This allows yeast to slowly decompose and transform the in-situ carbon layer covering the surface of the lithium manganese iron phosphate material, resulting in a carbon composite material. The inert gas protection prevents the material from oxidizing at high temperatures. The slow decomposition and carbonization of the yeast not only forms an in-situ carbon layer covering the surface of the lithium manganese iron phosphate material but also utilizes the internal structure of the yeast to create three-dimensional interconnected ion diffusion channels.
[0067] Furthermore, the carbonization process involves placing the core-shell composite structure in a quartz boat within a tube furnace, introducing high-purity argon or nitrogen as a protective atmosphere, heating it to a preset carbonization temperature at a heating rate of 1-5℃ / min, and holding it at this temperature for several hours, thereby achieving a high-temperature oxidation operation on the core-shell composite structure.
[0068] Specifically, the core-shell composite structure is placed in a tube furnace and subjected to high-temperature carbonization under the protection of high-purity inert gas. This process allows yeast to slowly decompose and transform the in-situ carbon layer covering the surface of the lithium manganese iron phosphate material, resulting in a carbon composite material. The process includes: placing the core-shell composite structure in a tube furnace, introducing high-purity inert gas for protection, heating to 300°C at a rate of 1-2°C / min, and holding at that temperature for 2 hours for slow pre-carbonization; slowly decomposing and transforming the yeast into an in-situ carbon layer, while simultaneously forming a mesoporous network; heating to 600-650°C at a rate of 2-5°C / min, and holding at that temperature for 6-12 hours for high-temperature crystallization and orientation locking, while simultaneously introducing anti-site defects of lithium, iron, and manganese elements, to obtain a carbon composite material with three-dimensional through-channel ion diffusion.
[0069] During the carbonization process, the core-shell composite structure is placed in a tube furnace and protected with a high-purity inert gas to create an oxygen-free environment. This prevents oxidation at high temperatures, ensuring the final carbon layer has high purity and a complete structure. The high-purity inert gas can be nitrogen with a purity of 99.999% or higher, with precise control of the gas flow rate to maintain a stable atmosphere within the furnace; alternatively, high-purity argon with a purity of 99.999% or higher can be used, utilizing its excellent inertness to effectively isolate the material from the influence of oxygen and water vapor. The temperature is raised to 300℃ at a rate of 1-2℃ / min and held at this temperature for 2 hours for slow pre-carbonization. The key to this step is controlling the yeast decomposition rate to avoid stress concentration and structural damage caused by rapid heating, thereby promoting the uniform conversion of yeast into a carbon layer and initially constructing a mesoporous network.
[0070] During the heat preservation period, the temperature fluctuation range of the tubular furnace can be controlled within ±5℃ to ensure the stability of the pre-carbonization process. In the slow pre-carbonization stage, the yeast slowly decomposes, and its organic matter gradually carbonizes, forming an in-situ carbon layer covering the surface of the lithium manganese iron phosphate material. Simultaneously, utilizing the yeast's biological template characteristics, a mesoporous network with specific morphology and connectivity naturally forms. This mesoporous network provides preliminary channels for subsequent ion diffusion. The pore size distribution and connectivity of the mesoporous network can be finely controlled by adjusting the initial state of the yeast (such as activation level and suspension concentration) and pre-carbonization conditions (such as heating rate and holding time). After pre-carbonization, the temperature is further increased to 600-650℃ at a rate of 2-5℃ / min and held at this temperature for 6-12 hours for high-temperature crystallization and orientation locking. This promotes the growth and structural stability of the lithium manganese iron phosphate crystals, while locking the crystal orientation to prevent structural collapse, thereby ensuring the long-term stability and integrity of the ion diffusion channels.
[0071] During high-temperature crystallization, antisite defects of lithium, iron, and manganese are introduced simultaneously by precisely controlling process parameters. This defect engineering aims to optimize the lattice arrangement and enhance the transport kinetics of lithium ions within the cathode material, thereby increasing their migration rate. The introduction of antisite defects can be achieved by adjusting the precursor ratio (e.g., slightly deviating from the stoichiometry) or controlling the atmosphere and cooling rate during high-temperature processing; alternatively, adding a small amount of specific dopant (such as a small amount of transition metal salt) during carbonization can induce the formation of antisite defects, further optimizing the crystal structure. After this series of precisely controlled carbonization processes, a carbon composite material is finally obtained, with an internal three-dimensional network structure composed of in-situ carbon layers containing interconnected mesopores and channels that are fully permeable throughout the material. The macroscopic morphology of this material maintains the spherical structure of the yeast template, while the microscopic structure consists of a hierarchical structure formed by primary nanoparticles and secondary micron-sized spherical particles. The internal channels are tightly wetted with the polymer electrolyte layer, together forming a highly efficient lithium-ion transport architecture.
[0072] Through a series of precisely controlled carbonization steps, the microstructure of lithium manganese iron phosphate cathode material was organically constructed and optimized. First, the core-shell composite structure was placed in a tube furnace and protected with high-purity inert gas. This provided an oxygen-free environment for subsequent high-temperature processing, effectively preventing oxidation of the material at high temperatures and ensuring the purity and integrity of the carbon layer and crystal structure. Next, pre-carbonization was performed by slowly heating to 300℃ at a rate of 1-2℃ / min and holding for 2 hours. This gentle heating rate and moderate holding time allowed the yeast template to decompose slowly and uniformly, avoiding stress concentration and structural damage caused by rapid decomposition, ensuring uniform coverage of the in-situ carbon layer and the initial formation of a mesoporous network. Based on this, the slow decomposition process of the yeast transforms itself into an in-situ carbon layer covering the surface of the lithium manganese iron phosphate material. Simultaneously, utilizing the inherent biological template characteristics of yeast, a well-connected mesoporous network was formed, providing initial diffusion channels for lithium ions. Subsequently, the temperature was further increased to 600-650℃ at a rate of 2-5℃ / min and held for 6-12 hours for high-temperature crystallization and orientation locking. This high-temperature treatment not only promotes the full growth and structural stability of lithium manganese iron phosphate crystals, but more importantly, it locks the crystal orientation, preventing structural collapse during subsequent use and ensuring the long-term stability and integrity of the ion diffusion channels. Simultaneously, during this high-temperature crystallization process, anti-site defects of lithium, iron, and manganese elements were introduced through precise process control. These defects optimize the lattice arrangement and significantly enhance the transport dynamics of lithium ions within the cathode material, thus synergizing with the external three-dimensional through-hole ion diffusion channels to jointly improve the overall migration rate of lithium ions. Through the above-mentioned interconnected and precisely controlled carbonization processes, this application successfully constructed a carbon composite material with a stable and efficient three-dimensional through-hole ion diffusion channel. This channel not only achieves full-domain connectivity in its structure but also optimizes ion transport within the material through defect engineering, thereby significantly reducing interfacial impedance and greatly improving the transport efficiency of lithium ions at low temperatures.
[0073] S6. The carbon composite material and nitrogen-doped graphene nanomaterials are mixed at a preset mass ratio, ultrasonically dispersed in ethanol for 30 minutes, vacuum dried, and then heat-treated at high temperature under an inert atmosphere to obtain a three-dimensional conductive network structure.
[0074] Nitrogen-doped graphene nanomaterials, acting as external conductive agents, co-construct a three-dimensional conductive network with in-situ carbon layers, significantly improving the electronic conductivity of the cathode material. Ultrasonic dispersion ensures uniform mixing of the two conductive materials. High-temperature heat treatment promotes the bonding of graphene and carbon composite materials, forming a stable conductive network. Besides ethanol, isopropanol or N-methylpyrrolidone (NMP) can also be used as dispersion solvents. After ultrasonic dispersion, spray drying or freeze-drying can be employed to maintain the porous structure of the material. High-temperature heat treatment can be carried out under a nitrogen atmosphere, and the heat treatment time can be appropriately extended to further enhance the formation of the conductive network.
[0075] S7. A positive electrode slurry is prepared by mixing a three-dimensional conductive network structure with additives. After coating, drying and rolling, a positive electrode substrate is obtained. The surface of the positive electrode substrate is modified to obtain a positive electrode sheet.
[0076] The positive electrode slurry comprises active materials, conductive agents, and binders. Coating, drying, and rolling are standard electrode fabrication processes used to form electrodes with specific thicknesses and densities. Interface modification aims to improve the compatibility between the positive electrode and the polymer electrolyte layer, and reduce interfacial impedance. During slurry preparation, a high-speed disperser can be used for mixing to ensure the uniformity and stability of the slurry. Coating can be performed using slot extrusion coating or blade coating. After drying, multi-stage rolling can be performed to gradually increase the electrode density. Interface modification can employ atomic layer deposition (ALD) technology to grow an ultrathin inorganic oxide layer on the positive electrode surface to improve interfacial stability.
[0077] S8. The negative electrode, polymer electrolyte layer, and positive electrode are stacked in sequence and then hot-pressed and sealed to obtain a lithium-ion polymer battery.
[0078] The components are assembled and packaged in a specific order to form a complete battery. Thermopressing ensures a tight fit between layers, reduces interfacial contact resistance, and provides excellent sealing. The negative electrode can be made of lithium metal foil. The polymer electrolyte layer can be formed through in-situ polymerization, where a liquid polymer precursor is first coated onto the electrode surface, and then cured by heating or ultraviolet light to form a solid electrolyte. After thermopressing, vacuum sealing can be performed to further improve the battery's sealing performance and stability.
[0079] Specifically, in this embodiment of the invention, an appropriate amount of commercial brewing yeast is weighed and dispersed in deionized water to prepare a yeast suspension. This suspension is then placed in a culture medium containing glucose, peptone, and yeast extract, and cultured with shaking at 30°C and 180 rpm for 24 hours. After the culture is complete, the culture medium residue and impurities are removed by centrifugation and washing several times, and the suspension is then resuspended in deionized water to obtain the activated yeast template suspension.
[0080] Next, lithium acetate, manganese acetate, ferric acetate, and ammonium dihydrogen phosphate were dissolved in deionized water in a Li:Mn:Fe:P molar ratio of 1:0.5:0.5:1 to prepare a precursor solution. At room temperature, the activated yeast template suspension was slowly added dropwise to the precursor solution at a rate of 0.5 mL / min using a peristaltic pump, while simultaneously magnetically stirring for 2 hours to obtain a homogeneous mixed solution.
[0081] Next, the above mixed solution was transferred to a reaction vessel and heated to 90°C at a rate of 2°C / min, and then held at this temperature for 3 hours. During this process, precursor ions nucleated and grew on the surface of the yeast cell wall, forming a yeast-precursor complex with nano-lithium manganese iron phosphate primary microparticles loaded on its surface.
[0082] Subsequently, after the reaction was completed at a constant temperature of 90℃, the pH of the mixed solution was adjusted and maintained at approximately 7.0 by adding dilute ammonia dropwise. The mixture was then slowly stirred at 150 rpm for 2 hours to promote the uniform coating and reassembly of the primary nanoparticles on the yeast surface. The resulting product was then centrifuged, washed, and dried in a vacuum oven at 60℃ for 12 hours to obtain a core-shell composite structure containing micron-sized secondary spherical particles.
[0083] The dried core-shell composite structure was then placed in a quartz boat within a tube furnace. First, high-purity argon gas was introduced for 30 minutes to purge the air. Then, the temperature was increased to 700°C at a rate of 3°C / min and held at 700°C for 6 hours for carbonization. During this process, the yeast template slowly decomposed, forming an in-situ carbon layer on the surface of the lithium manganese iron phosphate material. Simultaneously, the internal structure of the yeast transformed into three-dimensional interconnected ion diffusion channels, resulting in a carbon composite material.
[0084] Furthermore, the aforementioned carbon composite material was mixed with nitrogen-doped graphene nanomaterials at a mass ratio of 95:5. The mixture was then added to anhydrous ethanol and ultrasonically dispersed for 30 minutes using an ultrasonic processor to ensure uniform mixing. Subsequently, the dispersion was dried in a vacuum oven at 80°C and heat-treated at 600°C for 1 hour under a nitrogen atmosphere to obtain a composite material with a three-dimensional conductive network structure.
[0085] Furthermore, the composite material with the aforementioned three-dimensional conductive network structure was used as the active material and mixed with conductive carbon black and polyvinylidene fluoride binder at a mass ratio of 80:10:10. N-methylpyrrolidone solvent was added to prepare a uniform positive electrode slurry. The slurry was uniformly coated onto an aluminum foil current collector and dried in a vacuum oven at 80°C for 2 hours, then compacted to the target thickness using a roller press. Subsequently, a layer of PEO / Al2O3 nano-ceramic composite solution was uniformly sprayed onto the surface of the positive electrode substrate using a spraying method and dried at 60°C to obtain the interface-modified positive electrode sheet.
[0086] Finally, prepare the graphite anode sheet and the PEO-based solid polymer electrolyte membrane. Stack the graphite anode, polymer electrolyte membrane, and interface-modified cathode sheet sequentially. Place the stacked battery assembly in a hot press and hot-press it at 70°C and 0.8 MPa for 30 minutes, then vacuum seal it to obtain a low-temperature resistant lithium manganese iron phosphate battery.
[0087] Through the above technical solutions, the preparation method of this application significantly improves the lithium-ion and electron transport efficiency inside the cathode material by precisely controlling the formation of hierarchical microstructures and the construction of three-dimensional interconnected ion diffusion channels, combined with the three-dimensional conductive network formed by in-situ carbon layers and externally doped conductive agents. Simultaneously, interface modification of the cathode surface effectively improves the compatibility between the cathode and the polymer electrolyte layer, significantly reducing interfacial impedance. This comprehensive preparation strategy ensures that the prepared low-temperature resistant lithium manganese iron phosphate battery maintains high energy transfer efficiency and stable charge-discharge performance even at low temperatures, thus effectively solving the technical problems of high interfacial impedance and decreased lithium-ion transport efficiency in traditional manufacturing processes.
[0088] Commercial yeast was used as a biological template and activated to ensure its activity and stability, providing a uniform substrate for subsequent crystallization. A precursor solution was prepared according to a preset stoichiometric ratio and the yeast suspension was slowly added to control the material composition and mixing rate, preventing agglomeration and promoting uniform dispersion. The mixed solution was heated, utilizing the yeast cell wall as a crystallization site to form a composite loaded with primary nanoparticles, laying the foundation for a hierarchical structure. Maintaining a neutral environment and using slow stirring and vacuum drying ensured that the nanoparticles reassembled on the yeast surface to form a core-shell structure of micron-sized secondary spherical particles, achieving ordered construction at the microscopic level. High-temperature carbonization under inert gas protection decomposed the yeast into an in-situ carbon layer, forming a mesoporous network while preserving the permeability of the three-dimensional channels. The carbon composite material was mixed with nitrogen-doped graphene in a preset ratio and heat-treated to construct a three-dimensional conductive network, enhancing electron transport capabilities. A positive electrode slurry was prepared with additives and the interface was modified to directly optimize the positive electrode surface characteristics and reduce the interfacial impedance with the electrolyte. Finally, through stacking and hot-pressing encapsulation, all components were ensured to fit tightly together, forming a complete battery.
[0089] Those skilled in the art will understand that all or part of the steps in the various methods of the above embodiments can be implemented by a program instructing related hardware. The program can be stored in a computer-readable storage medium, which may include: read-only memory (ROM), random access memory (RAM), magnetic disk or optical disk, etc.
[0090] Furthermore, the embodiments of the present invention have been described in detail above. Specific examples have been used to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of the present invention. Therefore, the content of this specification should not be construed as a limitation of the present invention.
Claims
1. A low-temperature resistant lithium manganese iron phosphate battery, characterized in that, The low-temperature resistant lithium manganese iron phosphate battery includes: a negative electrode, a polymer electrolyte layer, a positive electrode, and an encapsulation layer arranged in layers from the inside to the outside. The positive electrode is based on lithium manganese iron phosphate as the active material. The lithium manganese iron phosphate material includes several primary nanoparticles and several secondary micron-sized spherical particles. The primary nanoparticles and the secondary micron-sized spherical particles form a hierarchical microstructure. The hierarchical microstructure contains a three-dimensional interconnected ion diffusion channel formed based on yeast template growth, and the three-dimensional interconnected ion diffusion channel achieves full-domain connectivity by relying on the hierarchical microstructure. The gaps between the primary nanoparticles and the secondary micron-sized spherical particles are interconnected based on the three-dimensional through-flow ion diffusion channels. The positive electrode is tightly bonded to the polymer electrolyte layer, which is immersed in the three-dimensional through-channel ion diffusion of the positive electrode, forming a high-speed lithium-ion transport architecture.
2. The low-temperature resistant lithium manganese iron phosphate battery as described in claim 1, characterized in that, The three-dimensional through-channel ion diffusion system comprises several mesopores and several channels, forming a network structure in which the mesopores and channels are interconnected. The porosity of the network structure is α, and the value of α ranges from 30% to 40%.
3. The low-temperature resistant lithium manganese iron phosphate battery as described in claim 1, characterized in that, The three-dimensional through-channel ion diffusion is formed based on an in-situ carbon layer, which covers the surface of the lithium manganese iron phosphate material of the cathode. The in-situ carbon layer is formed based on yeast template carbonization, and the in-situ carbon layer and the externally doped conductive agent of the positive electrode constitute a three-dimensional conductive network.
4. The low-temperature resistant lithium manganese iron phosphate battery as described in claim 3, characterized in that, The external conductive agent is graphene, and the mass ratio of the amount of graphene added to the lithium manganese iron phosphate is β, wherein the value of β is in the range of 4%≤β≤6%.
5. The low-temperature resistant lithium manganese iron phosphate battery as described in claim 1, characterized in that, The primary nanoparticle size of the lithium iron manganese phosphate material is d1, and the value of d1 is in the range of 50nm≤d1≤100nm. The particle size of the micron-sized secondary spherical particles is d2, and the value of d2 is in the range of 1μm≤d2≤5μm.
6. The low-temperature resistant lithium manganese iron phosphate battery as described in claim 1, characterized in that, A polymer interface modification layer is provided between the positive electrode and the polymer electrolyte layer; The interface modification layer is a PEO polymer layer made of Al2O3 nano-ceramic filler. The room temperature ionic conductivity of the interface modification layer is γ, and the value of γ is in the range of γ≥10. -4 S / cm.
7. A method for preparing a low-temperature resistant lithium manganese iron phosphate battery, characterized in that, The preparation method is used to prepare the low-temperature resistant lithium manganese iron phosphate battery as described in any one of claims 1 to 6, and includes the following steps: S1. Commercial yeast was used as a biological template to culture yeast in a culture medium, and the yeast raw material was activated to obtain an activated yeast template. S2. Prepare the precursor solution according to the preset stoichiometric ratio, and slowly add the activated yeast template suspension to the precursor solution at room temperature to obtain a mixed solution. S3. The mixed solution is heated to promote the formation of crystals on the cell wall of the yeast template by the precursor solution, and a yeast-precursor complex with nano-primary particles loaded on its surface is obtained. S4. Maintain the mixed solution in a neutral solution environment, stir slowly to promote the uniform coverage and reassembly of the primary nanoparticles on the yeast surface, and form a core-shell composite structure with micron-sized secondary spherical particles on the yeast template after vacuum drying. S5. The core-shell composite structure is placed in a tube furnace and subjected to high-temperature carbonization under the protection of high-purity inert gas, so that the yeast slowly decomposes and transforms the in-situ carbon layer covering the surface of the lithium manganese iron phosphate material to obtain a carbon composite material. S6. The carbon composite material and nitrogen-doped graphene nanomaterials are mixed at a preset mass ratio, ultrasonically dispersed in ethanol for 30 minutes, vacuum dried, and then heat-treated at high temperature under an inert atmosphere to obtain a three-dimensional conductive network structure. S7. The three-dimensional conductive network structure is combined with additives to prepare a positive electrode slurry. After coating, drying and rolling, a positive electrode substrate is obtained. The surface of the positive electrode substrate is modified to obtain a positive electrode sheet. S8. The negative electrode, polymer electrolyte layer, and positive electrode are stacked in sequence and then hot-pressed and sealed to obtain a lithium-ion polymer battery.
8. The method for preparing a low-temperature resistant lithium manganese iron phosphate battery as described in claim 7, characterized in that, The process involves culturing commercial yeast as a biological template in a culture medium, activating the yeast raw material, and obtaining the activated yeast template, which includes: The yeast raw material was dissolved in deionized water, and the initial solution was obtained by thorough stirring. The initial solution was centrifuged at 3000 rpm to remove impurities, and after several washing operations, a pure solution was obtained. The pure solution was dried in a vacuum environment to obtain the activated yeast template.
9. The method for preparing a low-temperature resistant lithium manganese iron phosphate battery as described in claim 7, characterized in that, The step of preparing the precursor solution according to a preset stoichiometric ratio and slowly adding the activated yeast template suspension to the precursor solution at room temperature to obtain a mixed solution includes: A precursor solution was prepared by dissolving lithium acetate, manganese acetate, ferric acetate, and ammonium dihydrogen phosphate in deionized water according to a molar ratio of Li:Mn:Fe:P of 1:0.5:0.5:
1. At room temperature, the activated yeast template suspension was slowly added dropwise to the precursor solution at a rate of 0.5 mL / min using a peristaltic pump, while magnetic stirring was performed continuously for 2 hours to obtain a homogeneous mixed solution.
10. The method for preparing a low-temperature resistant lithium manganese iron phosphate battery as described in claim 7, characterized in that, The core-shell composite structure is placed in a tube furnace and subjected to high-temperature carbonization under the protection of high-purity inert gas. This allows yeast to slowly decompose and transform the in-situ carbon layer covering the surface of the lithium manganese iron phosphate material, resulting in a carbon composite material comprising: The core-shell composite structure is placed in a tube furnace, protected by high-purity inert gas, and heated to 300°C at a rate of 1-2°C / min, and held at that temperature for 2 hours for slow pre-carbonization. The yeast is slowly broken down and transformed into an in-situ carbon layer, while simultaneously forming a mesoporous network; The temperature is increased to 600-650℃ at a rate of 2-5℃ / min, and held for 6-12 hours to carry out high-temperature crystallization and orientation locking. At the same time, antisite defects of lithium, iron and manganese elements are introduced to obtain carbon composite materials with three-dimensional through ion diffusion channels.